2022
DOI: 10.1002/oby.23600
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of GLP‐1RAs for the management of postprandial hypoglycemia following bariatric surgery: a systematic review

Abstract: Objective Postprandial hyperinsulinemic hypoglycemia with neuroglycopenia is an increasingly recognized complication of Roux‐en‐Y gastric bypass and gastric sleeve surgery that may detrimentally affect patient quality of life. One likely causal factor is glucagon‐like peptide‐1 (GLP‐1), which has an exaggerated rise following ingestion of carbohydrates after bariatric surgery. This paper sought to assess the role of GLP‐1 receptor agonists (GLP‐1RAs) in managing postprandial hypoglycemia following bariatric su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
(163 reference statements)
0
7
0
Order By: Relevance
“… 3 The significant interplay between these two conditions deserves its due attention, with globalisation and social development accelerating the modern obesogenic environments that precede the obesity epidemic and the incidence of non-communicable diseases. 22 …”
Section: Discussionmentioning
confidence: 99%
“… 3 The significant interplay between these two conditions deserves its due attention, with globalisation and social development accelerating the modern obesogenic environments that precede the obesity epidemic and the incidence of non-communicable diseases. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Much attention has been given in the past decades to incretin hormones such as glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic peptide (GIP), both being gut peptides released from the more proximal small bowel and known to stimulate insulin secretion after a hyperglycemic spike resulting in reactive hypoglycemia. [14][15][16] Postprandial hypoglycemia (PPH) occurs more often after bariatric surgery. 5,17,18 A recent study that used continuous glucose monitoring (CGM) found a prevalence of PPH after bariatric surgery of up to 50% in patients who had undergone Roux-en-Y gastric https://doi.org/10.2147/CEG.S392265…”
Section: Pathophysiology Of Dumping Syndromementioning
confidence: 99%
“…Given that the pathophysiology of dumping syndrome is partly due to glucagon-like peptide-1 (GLP-1; a gut-derived incretin hormone secreted by the L cells mainly found in the ileum that stimulate insulin secretion from the pancreatic β cells), it was suggested that antagonizing the action of GLP-1 may lead to a reduction in postprandial hypoglycemic events. 16 Although the exact mechanism remains unclear, we know from studies on glucagon-like peptide-1 receptor agonists (GLP-1RAs) in type 2 diabetes mellitus patients that GLP-1RAs delay gastric emptying, reduce postprandial hyperglycemia, promote insulin secretion, reduce β-cell workload and intestinal glucose absorption, and delay nutrient transit through the small intestine. GLP-1RAs avoid a postprandial peak in insulin release by mimicking native GLP-1 and blocking the GLP-1 receptor (as they are resistant to dipeptidyl peptidase-4 breakdown) and therefore may reduce hyperinsulinemic hypoglycemia episodes after bariatric surgery, as was recently analyzed in a systematic review.…”
Section: New Perspectives In Medical Interventionsmentioning
confidence: 99%
“…65,66 Therefore, GLP-1 which enhances insulin secretion, can lead to the effect of postprandial glucagon release and satiety. 67 Turning to the insulin-related effects of GLP-1, it enhances insulin secretion and also affects insulin resistance through its effects, such as increasing the expression of glucose transporters in insulin-dependent tissues, and playing a role in lipid metabolism modulation, inflammation, and oxidative stress reduction. [68][69][70] GLP-1 can also improve some comorbidities like polycystic ovary syndrome (PCOS).…”
mentioning
confidence: 99%